Relationship With the Father of the Baby and Perceived Stress Among Black Women. Issue 5 (September 2018) - Eboh, Relicious N.; Giurgescu, Carmen; Misra, Dawn P.
Abstract: Objective: The purpose of this study was to examine whether the relationship with the father of the baby was related to psychological stress among Black women. Methods: This is a secondary analysis of data derived from a retrospective cohort study of 1, 410 Black new mothers participating in the Life-course Influences on Fetal Environments (LIFE) study conducted in the Detroit Metropolitan area. Data were obtained from maternal interview and medical records abstraction. Perceived stress was measured by the Cohen's Perceived Stress Scale. The mother's relationship with the father of the baby before and after pregnancy was measured using two questions. Results: Women who reported sometimes close/sometimes distant relationship with the father of the baby prior to pregnancy had higher levels of perceived stress compared with women who reported close relationship with the father of the baby prior to pregnancy (38.73 and 35.10, respectively, p < .001). Women who reported current distant relationship (38.82 and 34.45, respectively, p < .001) and sometimes close/sometimes distant relationship (38.83 and 34.45, respectively, p < .001) reported higher levels of perceived stress compared with women who had current close relationship with the father of the baby. Clinical Implications: Women who reported to have a close relationship with the father of the baby before and during the pregnancy reported lower levels of stress compared with women with a distant relationship with the father of the baby. Nurses should assess women's relationship with the father of the baby and their levels of stress. Abstract : The relationship with the father of the baby may influence psychological well-being of pregnant women. In this study, women who reported distant relationship with the fathers of their babies during pregnancy had higher levels of perceived stress. As stress is known to affect pregnancy outcomes, this type of information obtained during initial and ongoing assessment during pregnancy can help to guide supportive nursing care and appropriate referral.